(-6-6i)-(5+i)=

Simple and best practice solution for (-6-6i)-(5+i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-6-6i)-(5+i)= equation:


Simplifying
(-6 + -6i) + -1(5 + i) = 0

Remove parenthesis around (-6 + -6i)
-6 + -6i + -1(5 + i) = 0
-6 + -6i + (5 * -1 + i * -1) = 0
-6 + -6i + (-5 + -1i) = 0

Reorder the terms:
-6 + -5 + -6i + -1i = 0

Combine like terms: -6 + -5 = -11
-11 + -6i + -1i = 0

Combine like terms: -6i + -1i = -7i
-11 + -7i = 0

Solving
-11 + -7i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + -7i = 0 + 11

Combine like terms: -11 + 11 = 0
0 + -7i = 0 + 11
-7i = 0 + 11

Combine like terms: 0 + 11 = 11
-7i = 11

Divide each side by '-7'.
i = -1.571428571

Simplifying
i = -1.571428571

See similar equations:

| X+3=2*x | | 3(b+1)=4b-2(-3) | | 2x-7/x=x-2/5 | | 0.05(5-7x)=8-(4x+6) | | (3x+2)(4x^2-5x-3)= | | (4x+35)= | | 24=x/1 | | 27a^12= | | 49p^4-84p^2+36=0 | | x+3(x+2)=2(x+1)+20 | | 13x-3x=-60 | | P=(20+05x)+0.15(20+0.5x) | | 15=-3(3+4) | | f(x)=cos(7x+5) | | 0.2a+9=11.4 | | Cos((pi/3)/x) | | y-80=1.357(x-0) | | (4x+3y+1)dx+(x+y+1)dy=0 | | 5c/6-c/6 | | (D^6+1)y=0 | | h=-16t^2+224t+1152 | | V-7b=3 | | log[2](5x-2)=3 | | 100-P=-20+2P | | 88/2 | | 5+3*x=47 | | 1.56=logx | | 2(x+1)=3x-8 | | 3n^2+2n=0 | | x-9=-7+8 | | 10(6+y)+11y=149 | | x^2+4x+4=32 |

Equations solver categories